Using key passages to understand literature, theory and criticism - Laga, Barry (Routledge, Taylor & Francis Group, 2019)
a"An Introduction to Theory and Criticism is a completely fresh and innovative approach to teaching and learning literary theory: using short passages of theory to make sense of literary and cultural texts. It focuses on the key concepts that help readers understand literature and cultural events in new and provocative ways. Covering a wide variety of iconic and contemporary theorists, this offers a broad chronological and global overview. The book includes 30 "passages" from theorists such as Victor Schklovsky, Roland Barthes, Judith Butler, Diana Fuss, Jean Baudrillard, Kwame Anthony Appiah, Michel Foucault, Laurence Buell, Eve Sedgwick, and many more. Built on the premise that scholars use theory pragmatically, An Introduction to Theory and Criticism identifies problems, puzzles, and questions readers may encounter when they read a story, watch a film, or look at art. It explains in detail 30 concepts that help readers make sense of these works, and invites students to apply the concepts to a range of writing and research projects. The textbook concludes by helping students read theory with an eye on finding productive passages and writing their own "theory chapter," signaling a shift from student as critic to student as theorist. Used as a main text in introductory theory courses or as a supplement to any literature, film, theatre, or art course, this book helps students read closely and think critically."- Provided by publisher.